The Effect of Awards and Work Spirit on The Performance of Employees PT. Candi Baru Sugar Factory, Sidoarjo - Emmywati (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
Management is the science and art that regulates the process of utilizing human resources effectively and efficiently to achieve the desired goals. Quality is not only smart, but can meet all the qualitative requirements that the job requires, so that the work can be completed according to plan This research carried out to improve the quality of human resources through appreciation and work enthusiasm at PT. Candi Baru Sugar Factory, Sidoarjo. This research was conducted on 60 employees using questionnaires and SPSS data processing (quantitative research method). The results of this research that has been done, and it shows that appreciation and morale partially and simultaneously have a positive effect on employee performance (Adjusted R Square shows a value of 0.837 or 83.7%), while morale is the dominant factor.